Genetics and epigenetics of small bowel adenocarcinoma: the interactions of CIN, MSI, and CIMP - Warth, Arne; Kloor, Matthias; Schirmacher, Peter; Bläker, Hendrik (Modern pathology, 2011)
Characterization of tumor genetics and epigenetics allows to stratify a tumor entity according to molecular pathways and may shed light on the interactions of different types of DNA alterations during tumorigenesis. Small intestinal adenocarcinoma is rare, and to date the interrelation of genomic instability and epigenetics has not been investigated in this tumor type. We therefore analyzed 37 primary small bowel carcinomas with known microsatellite instability and KRAS status for chromosomal instability using comparative genomic hybridization, for the presence of aberrant methylation (CpG island methylation phenotype) by methylation-specific polymerase chain reaction, and for BRAF mutations. Chromosomal instability was detected in 22 of 37 (59%) tumors (3 of 9 microsatellite instable, and 19 of 28 microsatellite stable carcinomas). Nine carcinomas (24%) were microsatellite and chromosomally stable. High-level DNA methylation was found in 16% of chromosomal instable tumors and in 44% of both microsatellite instable and microsatellite and chromosomally stable carcinomas. KRAS was mutated in 55, 0, and 10% of chromosomal instable, microsatellite instable, and microsatellite and chromosomally stable tumors, respectively whereas the frequencies of BRAF mutations were 6% for chromosomal instable and 22% for both microsatellite instable and microsatellite and chromosomally stable carcinomas. In conclusion, in this study we show that chromosomal instable carcinomas of the small intestine are distinguished from microsatellite instable and microsatellite and chromosomally stable tumors by a high frequency of KRAS mutations, low frequencies of CpG island methylation phenotype, and BRAF mutations. In microsatellite instable and microsatellite and chromosomally stable cancers, CpG island methylation phenotype and BRAF/KRAS mutations are similarly distributed, indicating common mechanisms of tumor initiation or progression in their molecular pathogenesis.
Gesehen am 08.11.2022